THE USE OF THE MEDIA MATERIALS OF THE PERIOD OF THE GREAT PATRIOTIC WAR IN THE PATRIOTIC EDUCATION OF MODERN YOUTH (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-201-210Abstract. The article is devoted to the practice of using domestic print media, radio plots and related media products of the 1940s in the work of the centers of patriotic education in Krasnodar. The transformation of the content and presentation of media materials created during the Great Patriotic War for ideological work with young people is considered.Key words: history of journalism, ideology of mass media, youth policy, patriotic education